2019
DOI: 10.1080/02640414.2019.1702282
|View full text |Cite
|
Sign up to set email alerts
|

A bioecological perspective on talent identification in junior-elite soccer: A Pan-European perspective

Abstract: Elite soccer clubs across Europe spend ever-increasing sums of money on transfers and salaries for worldclass players. Consequently, clubs' talent identification and development processes for junior players have become more professionalised. Based on a holistic ecological approach, this study presents an analysis of talent identification practices across some of the most productive soccer academies in Europe (N = 11). Data were collected via semi-structured interviews with 11 heads of academy recruitment from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Thus, the design and implementation of appropriate programs to uncover youth soccer players' potentials are common practice within soccer academies. These academies support the early development [4] and then the transition of young players into the senior professional world [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the design and implementation of appropriate programs to uncover youth soccer players' potentials are common practice within soccer academies. These academies support the early development [4] and then the transition of young players into the senior professional world [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The findings reported a significant selection bias when no-age group information was presented, however, the selection bias was eliminated when participants had access to the players' relative age, in the form of age-ordered shirt numbering. Evidence, that this pragmatic research is filtering its way into the performance domain was illustrated recently in a holistic ecological analysis of talent recruitment and development environments from eleven of the most successful elite soccer academies across Europe (Reeves & Roberts, 2019). Indeed, data indicated that the RAE was understood by all the clubs and pedagogical age group modification strategies similar to those reported by Mann and colleagues (2017) were employed during real-time scouting assignments.…”
Section: Hypothesis Driven "Pragmatic" Research Designs To Move the Debate Forwardmentioning
confidence: 79%
“…From a biological perspective, variations between chronological age and biological maturation (i.e. relatively older vs late maturing) are reported to be understood by a number of Europe's leading academies and, in some cases, estimates of skeletal maturity are in place to measure and monitor players classified as late, average or early maturity according to birth date quarter (Reeves & Roberts, 2019). One club was employing bio-banding strategies (Cumming et al, 2017) where players were grouped by estimated biological maturity status (Kharmis & Roche, 1994) for specific competitions and training once maturity variances were observed.…”
Section: Bio-bandingmentioning
confidence: 99%
“…That is, considering the use of Bronfenbrenner and the theory underpinning organisational culture could help develop the HEA and allow better testing of the approach. It is increasingly important to have these considerations since the HEA now underpins Dual Career Development Environment research (Henriksen et al, 2020), talent identification research (Reeves & Roberts, 2020), and community research (Balish & Côté, 2014). Also, considering the way we classify successful environments might need a rethink.…”
Section: Concluding Remarks and Limitationsmentioning
confidence: 99%